The synergy of leadership, motivation, and training in boosting employee performance: A case analysis of The KRU - Harmini, AA Ayu Ngr.; Rastitiati, Ni Kade Juli; Mandang, Selvie Ratna Ivone; Putra, I Komang Mahayana; Sekarti, Ni Ketut (Journal of Commerce, Management, and Tourism Studies, 2024)
Employee performance in the hospitality industry is significantly influenced by leadership style, motivation, and job training. The KRU, as a luxury destination in Bali, needs to understand these factors to enhance employee performance and guest services. This study aims to analyse the impact of leadership style, motivation, and job training on employee performance at The KRU. This research employs a quantitative method with a survey approach. Data was collected through questionnaires distributed to the resort's employees. Data analysis utilized descriptive statistics and regression analysis to assess the relationships between variables. The analysis results indicate that supportive leadership styles and high motivation significantly affect employee performance improvement. Additionally, effective job training contributes to enhanced skills and productivity among employees. Leadership style, motivation, and job training have a significant positive impact on employee performance. Recommendations are provided to enhance leadership approaches and training programs to maximize employee performance.